Impact of APOE‐ε4 on cerebral amyloid deposition in participants with abnormal soluble amyloid levels: Amyloid imaging. (7th December 2020) - Cacciaglia, Raffaele; Molinuevo, Jose Luis; Salvadó, Gemma; Suárez‐Calvet, Marc; Shekari, Mahnaz; Operto, Greg; Fauria, Karine; Minguillón, Carolina; Farrar, Gill; Buckley, Chris J; Blennow, Kaj; Zetterberg, Henrik; et al.
Abstract: Background: Amyloid pathology can be detected using cerebrospinal fluid (CSF) biomarkers and positron emission tomography (PET) imaging, even though they measure two distinct beta‐amyloid (Aβ) pools. While CSF Aβ concentrations reflect the clearance of soluble amyloid species from the brain, PET imaging informs on the presence of insoluble fibrillary plaques in the brain tissue. Many studies have shown the concordance between the two measures in individuals along the Alzheimer's continuum. Here, we assessed whether APOE‐ε4, the major genetic risk factor for Alzheimer's disease (AD), affects the pattern of cerebral Aβ load as a function of CSF Aβ levels. Method: The first consecutive 276 cognitively unimpaired (CDR = 0) individuals of the ALFA+ study, aged between 48 and 74, with valid structural MRI and [ 18 F]flutemetamol (FTM) PET, APOE genotyping and CSF samples were included. Aβ40 and Aβ42 concentrations were determined with the Roche NeuroToolKit (Roche Diagnostics) and parametric standardized uptake value ratio images (SUVr) were calculated with the whole cerebellum as reference region. A voxel‐wise regression was performed to predict FTM uptake, with the following independent variables: age, sex, APOE‐ε4, and CSF Aβ42/40 ratio. Statistical threshold was set to p < 0.001 with a cluster extent correction of 100 voxels. Result: As expected, CSF Aβ42/40 ratio was negatively associated with cerebral FTM uptake (Figure 1a‐1b). Age and APOE‐ε4 gene dose mapped onto distinct spatial patterns of FTM‐binding across the whole sample (Figure 2b‐2c). Importantly, we found a significant interaction between CSF Aβ42/40 and APOE‐ε4 indicating that carriers had a negative association between fluid and imaging Aβ measures in the bilateral hippocampus, as well as the bilateral middle temporal and temporo‐parietal junction (Figure 3). Conclusion: Compared to non‐carriers, APOE‐ε4 carriers showed higher cerebral Ab load for any given level of CSF Aβ42/40 in areas that are not typically vulnerable to Aβ deposition yet undergoing neurodegeneration early in the Alzheimer's continuum, such as the hippocampus. This suggests that APOE‐ε4 may influence the biological mechanisms regulating the equilibrium between soluble and deposited amyloid, which may transcend the hindering effect caused by Aβ fibrillary plaques and render medial temporal lobe structures particularly vulnerable when Aβ metabolism becomes deficient.